N2O Emissions From Residues of Oat and Grass Pea Cover Crops Cultivated in the US Southern Great Plains - Singh, Hardeep; Kandel, Tanka P.; Gowda, Prasanna H.; Northup, Brian K.; Kakani, Vijaya G. (Frontiers in Sustainable Food Systems, 2021)
Grass pea (Lathyrus sphaericus) and oat (Avena sativa) are potential cover crops for spring periods of summer crop systems in the US Southern Great Plains (SGP). The main objective of this study was to compare nitrous oxide (N2O) emissions from residues of grass pea and oat grown as green nitrogen (N) crops. The comparisons included responses from plots cultivated with oat, grass pea, and control (spring-fallowed) plots. Two management options were applied to grass pea: residues retained and aboveground biomass removed for forage. Crabgrass (Digitaria sanguinalis) was cultivated as a main summer crop immediately after termination of the cover crops. Fluxes of N2O were measured by closed chamber connected to a portable gas analyzer on 23 dates during a 3 month growing period for crabgrass. At termination, oat produced more aboveground biomass than grass pea (2.17 vs. 3.56 Mg ha−1), but total N in biomass was similar (102–104 kg ha−1) due to greater N concentrations in grass pea than oat (4.80% vs. 2.86% of dry mass). Three month cumulative emissions of N2O from grass pea-incorporated plots (0.76 ± 0.11 kg N2O-N ha−1; mean ± standard error, n = 3) were significantly lower than from oat-incorporated plots (1.26 ± 0.14 kg N2O-N ha−1). Emissions from grass pea plots with harvested biomass (0.48 ± 0.04 kg N2O-N ha−1) were significantly lower than those from grass pea-incorporated plots. Cumulative N2O emissions from control plots were significantly greater than those from grass pea-harvested plots but were similar to the emissions from grass pea-incorporated plots. Yields produced by crabgrass were similar from all cover crop treatments (8.65–10.46 Mg ha−1), but yield responses to the control (18.53 Mg ha−1) were significantly larger. Nitrogen concentrations in crabgrass were greater in response to oat- and grass pea-incorporated plots (2.86–2.87%) than in grass pea-harvested (1.93%) and control (1.44%) plots. In conclusion, the results indicated that (i) post-incorporation emissions of N2O can be greater from a non-legume green N crop than a legume green N crop due to greater biomass productivity of the cereal, and (ii) emissions of N2O could be mitigated by removing biomass of the green N crop for use as forage.